2008
DOI: 10.1186/1532-429x-10-21
|View full text |Cite
|
Sign up to set email alerts
|

Time course of eosinophilic myocarditis visualized by CMR

Abstract: We report the diagnostic potential of cardiovascular magnetic resonance (CMR) to visualize the time course of eosinophilic myocarditis upon successful treatment. A 50-year-old man was admitted with a progressive heart failure. Endomyocardial biopsies were taken from the left ventricle because of a white blood cell count of 17000/mm 3 with 41% eosinophils. Histological evaluation revealed endomyocardial eosinophilic infiltration and areas of myocyte necrosis. The patient was diagnosed with hypereosinophilic myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 3 publications
2
53
0
Order By: Relevance
“…The subendocardium is generally not involved, with the exception of eosinophilic myocarditis, which frequently involves the endomyocardium (Figure 7a). (Bohl et al, 2008;Deb et al, 2008). In chronic myocarditis, besides an increased edema on T2-weighted imaging, an increased global relative enhancement is a common finding as confirmed in immunohistological analyses.…”
Section: Ce-cmr In Myocarditis 331 Myocarditismentioning
confidence: 64%
“…The subendocardium is generally not involved, with the exception of eosinophilic myocarditis, which frequently involves the endomyocardium (Figure 7a). (Bohl et al, 2008;Deb et al, 2008). In chronic myocarditis, besides an increased edema on T2-weighted imaging, an increased global relative enhancement is a common finding as confirmed in immunohistological analyses.…”
Section: Ce-cmr In Myocarditis 331 Myocarditismentioning
confidence: 64%
“…In fact, different scenarios have been reported in the course of active myocarditis in HES including the complete resolution of myocarditis and persistence of LGE lesions in the myocardium. 10,28,36 In addition, both scenarios were also observed in other types of myocardial inflammation, including vasculitis and viral etiology, and were linked to prognosis. 31,32 Prior case reports documented the ability of CMR to depict eosinophilic myocarditis in HES confirmed by endomyocardial biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Prior case reports documented the ability of CMR to depict eosinophilic myocarditis in HES confirmed by endomyocardial biopsy. 9,25,28 In the current study, despite the apparent clinical and laboratory control of disease, 3 women demonstrated CMR evidence of myocarditis. Of note, CMR abnormalities were associated with higher levels of blood eosinophil count, that reflects the role of eosinophils in myocardial inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography is often unremarkable in the acute phase of eosinophilic myocarditis [8], and CMRI can be useful in detecting the disease at an early stage [9]. Endomyocardial biopsy is often useful in confirming a diagnosis of CM and was considered in this case, but was deferred given the high associated risk in the setting of recent cardioembolic strokes and the consequent ongoing need for anticoagulation.…”
mentioning
confidence: 99%